Media barometer 1991 - Radio Sweden (Radio Sweden, 1998)
The first Media Barometer was conducted in 1979 and since then the survey has been carried out annually. The purpose is to explore how the Swedish population is using different media during an average day. In 1991 the respondents were asked if they had been listening to a record player or a tape recorder the day before. If so, they were asked for how long period. Respondents answering that they did not listen to record player or tape recorder the day before were asked when they last did so. All respondents were asked if the had been reading any of the following the day before: morning paper, evening paper, weekly magazine, comics or any other magazine, or book. If so, they were asked how many and for how long period. Book readers were also asked if they were reading the books for their own pleasure or if it was study literature. Those respondents who answered that they did not read any paper, magazine or book the day before were asked when they last did so. Furthermore respondents were asked about their radio listening habits including which channel the respondent listened to and if he/she listened to their local radio station or any foreign radio station. Respondents answering that they did not listen to the radio the day before were asked when they last listened to the radio. There is also information on access to equipment such as remote control, text television, stereo television, video recorder, satellite television, or parabolic aerial. Other information deals with the respondent´s possibility to watch Danish, Finnish and Norvegian television channels as well as TV4, channel 5, or local television. Background variables includes information on age, gender, education, occupation, and household composition.

Purpose:

Describe the trends and changes in people's use of mass media.

Mediebarometern genomfördes första gången 1979 och har sedan dess genomförts varje år. Undersökningen avser att belysa hur stor andel av den svenska befolkningen som en genomsnittlig dag tagit del av ett antal enskilda medier. Syftet är att beskriva tendenser och förändringar i människors utnyttjande av massmedier.

Syfte:

Beskriva tendenser och förändringar i människors nyttjande av massmedier.
Mediebarometern 1991
Keywords: newspaper readership; tidnings läsekrets; periodicals readership; tidskrifts läsekrets; listening to music; musiklyssnande; book use; bokanvändning; local broadcasting; lokalsändningar; radio stations; radiostationer; satellite television; satellit-tv; television channels; tv-kanaler; households; hushåll; radio listening; radiolyssnande; reading (activity); läsande; Media; Media; Social Sciences; Samhällsvetenskap; Media and Communication Studies; Medie- och kommunikationsvetenskap